Enhancing Edge Detection with an Optimized Canny Algorithm, Hough Transform, and Machine Learning Integration - K. Lafta, Russel; N. Sultani, Zainab (Al-Nahrain Journal of Science, 2025)
This paper addresses the challenge of accurate edge detection in image data, particularly in noisy and complex environments, by proposing a hybrid approach that combines classical and advanced techniques. An optimized Canny edge detection algorithm is first applied to enhance precision by reducing noise and improving edge continuity. Following this, the Hough Transform is used to extract geometric shapes, such as lines, due to its robustness against irregularities. To further improve detection accuracy, machine learning (ML) models are integrated, enabling the system to adapt and learn from the data. Experimental results on 50 images from BSD dataset show that the proposed hybrid method surpasses standalone techniques, achieving an accuracy of 88.47%, a precision of 29.79%, a recall of 38.55%, and an AUC of 0.80 using XGBoost. This combination of classical image processing methods and ML demonstrates significant improvements in edge extraction performance, making it a reliable solution for edge detection in diverse and noisy image datasets.